Energy Aware Routing Mechanism (EARM) for Effective Communication in Internet of Things (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Advancements and wide range of applications of computing and networking create the innovative origination of the notion called Internet of Things (IoT) which enables  varieties of devices and objects to connect and communicate via diverse communication medium. The sensors and the actuators are the fundamental building devices of IoT apart from the devices which are directly communicating with the humans. The devices exist with constrained capabilities like limited power like batteries and constrained processing power. As the devices are power-constrained and deployed in a large scale, establishing an energy efficient route among the devices is a challenging task. Frequent use of particular route for data transformation drains out the batteries very quickly. Many research works as stated in this paper, revealed that IoT needs mechanisms which effectively utilizes the energy of the node for effectual routing. This research work concentrates on the energy of the devices to be effectively utilized for a better routing among the devices. The proposed mechanism is simulated and compared with the existing research works which resulting in improved routing experience.